The University Bus Tracking System Employs the Internet of Things - Bahrum, Muhammad Ikhwan Hafiz (Journal of TVET and Technology Review, 2024)
Transportation serves as an efficient means of travel. In the current age of globalisation, transit is essential for a nation's economic progress. The legal foundation for accountability in a public service company now mandates the provision of exceptional and high-quality service. At now, students, especially those lacking personal transport, depend on school-provided transit to traverse the campus. However, a problem arose when students could not access the position and location while the bus was in transit. Users experience challenges stemming from the unpredictability of the bus's arrival timetable, resulting in an indeterminate waiting duration. We created an Internet of Things (IoT)-based bus tracking system for Universiti Tun Hussein Onn Malaysia (UTHM) to address the issue. This system allows users to effortlessly obtain real-time data regarding the bus's present location, position, and projected arrival time at each stop. The investigator employed the Design Thinking Process (DTP) framework in this investigation. The procedure comprises five stages: empathy, decision-making, ideation, prototyping, and testing. The findings of the analysis confirm the successful development and intended operation of the system. Moreover, the system can accurately display the bus's position and location while also offering valuable information to users. The following questionnaire substantiates this assertion, indicating that 32 students, including 95% of the target demographic, exhibit confidence in the product's functionality. Ultimately, UTHM's IoT-enabled bus tracking system effectively accomplished all its established objectives.